Relative contributions of bleeding scores and iron status on health‐related quality of life in von Willebrand disease: a cross‐sectional study. Issue 1 (9th September 2016) - Xu, Y.; Deforest, M.; Grabell, J.; Hopman, W.; James, P.
Abstract : Introduction: von Willebrand disease (VWD) is the most common inherited bleeding disorder known in humans. Currently, studies investigating the health‐related quality of life (HR‐QoL) in VWD using standardized tools are limited, particularly among patients with mild decreases in von Willebrand factor or activity. Aim: To determine HR‐QoL and its predictors among patients with mild, moderate and severe forms of VWD. Methods: Patients with clinical diagnosis of VWD were recruited from a tertiary Inherited Bleeding Disorder Clinic. Upon informed consent, bleeding scores were obtained via a standardized, self‐administered tool. Each participant also completed a HR‐QoL questionnaire (SF‐36). Analyses included paired t ‐test, independent t ‐test, one‐wayanova and multivariate regression. Results: A total of 102 patients were recruited (consent rate = 95%). Participants were 38 years on average (SD 14.8), 78% were female and 80% were diagnosed with VWD Type 1. Compared to age‐ and sex‐matched normative data, VWD patients had clinically and statistically significant reductions in seven of eight HR‐QoL domains and the physical and mental component summaries. Adjusted for age, sex, socioeconomic status and rurality, there was a trend towards lower physical component summary with increasing bleeding score, and lower mental domains with iron deficiency status ( P = 0.07 and P = 0.08 respectively). Conclusion: This study is the first to examine the impact of VWD on HR‐QoL across disease severity while incorporating socioeconomic status and rurality. Significant reductions in HR‐QoL among VWD patients, especially the relationship between iron status and mental HR‐QoL, strengthen the rationale for prospective studies to evaluate the efficacy of iron replacement in this setting.